Strengthening CARICOM's capacity to implement harmonised standards for agricultural and agro-industrial products and services : proposal for Caribbean Regional Human Resource Development Programme for Economic Competitiveness (CPEC) (CCS GeorgetownGY, 2002)
Seeks to strengthen CARICOM's capacity to develop and implement harmonised standards and metrology procedures for enhancing productivity and quality of agricultural and agro-industrial products and services, with the aim of facilitating trade within the Community and with third states, and also with the aim of protecting consumers and the natural environment.
Located in the filing cabinet.